Implementasi Perda No 2 Tahun 2012 Tentang Retribusi Pelayanan Pasar Di Kota Semarang (Studi Kasus Pasar Johar) - Sundari Yuwan Angelia; Aloysius Rengga; Slamet Santoso (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
The Government of Semarang city through Perda No. 2 / 2012 about Retribution Market service in Semarang City which is a case study in order to maximize the service of the Johar market. There are many problems in Johar market as the facility is the merchants and residents that is not good they paid retribution, not just in time it found the situation worse in the program, public order and security. Interestingly the fare in pay is not in accordance with Perda No. 2 / 2012 already set in . Based on, the writers interested researched about Retribution Market service in Semarang City which is a case study Johar market. This research is guided by theory belongs Riant Nugroho with 5 precision this is appropriatness of the policy, implementation, enviroment, targets and process to know Perda No. 2 / 2012 about Retribution Market service in Semarang City which is a case study Johar market. To find out by factors in support and inhibitors of the implementation of market levies for the writer holding on to the theory of edward III who consists of resources factor, communication factors, disposition factors, and the bureaucratic structure factors. Researchers used a qualitative approach. The result of suggests that there are still some things should be improved in the process of policy that the awareness of traders in order to carry out retribution, there are many officers not firmly, levy charges must be consistent with the policy set, officers are still the slow and agencies involved to finish problems. While a factor that impeding policy this is not consistent in the implementation of the job, who had not realized that other agencies are reponsible for this policy together, the officers misscommunication between traders and lack of awareness of traders. Giving advice to the writer is the levy to be adjusted, the provision of the facilities must be optimized, officers must firmly, additional security personnel, employeess enhanced quality and quantity, and coordination with related agencies must be done in optimally.